Institutional Quality, Trust and Stock-Market Participation: Learning to Forget - Hossein Asgharian; Lu Liu; Frederik Lundtofte (Lund University, School of Economics and Management, Department of Economics, 2014)
We explore the relation between institutional quality, trust and stock-market participation. In our theoretical model, agents update their beliefs in a Bayesian manner based on observations on frauds and choose whether to invest in the stock market. The corresponding empirical model shows that institutional quality affects trust and that the part of trust that is explained by institutional quality influences stock-market participation. For immigrants, we consider learning factors, such as education and duration of stay, and we find that the impact of the institutional quality of the country of residence, relative to that of the home country, tends to increase with education.
Keywords: C13; G11; 330; institutional quality; learning; trust; stock-market participation